A writer's guidebook - Axelrod, Rise B.; Cooper, Charles Raymond 1934-. (New York St. Martin's Press, 1998)
[This] is a brief reference handbook that offers help with the research and writing you will be asked to do in college and in your career.... It includes guidelines and basic information that will help you plan, research, write, edit, and present any essay or research project. -Introd.
Writing in college -- Researching in college -- Designing documents -- Sentence boundaries -- Grammatical sentences -- Effective sentences -- Word choice -- Punctuation -- Mechanics -- Brief guide for ESL writers -- Sentence structure -- Glossary of usage.
"With 1998 MLA guidelines for citing Web sources"--Cover p. [i]
Includes bibliographical references (p. 456) and index.
Keywords: English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc